A STUDY OF THE STRUCTURE OF WOOD DAMAGED BY ROT USING NUCLEAR MAGNETIC RESONANCE - Onuchin, Evgeny; Medyakov, Andrey; Grunin, Leonid; Sidorova, Elena (Journal of Applied Engineering Science, 2018)
Up-to-date production of fuel pellets has problems associated primarily with insufficient amount of raw material of high quality and its high cost. To increase the productivity of the pelletizing process, it is necessary to use defective trees including those affected by rot. In order to solve the problem of lack of strength of pellets, technical lignin is used as an additive. Various ways to determine the damage rate of wood by rot were investigated in order to know the amount of lignin needed to add to produce a product of high quality. The NMR relaxation method is characterized by simplicity of sample preparation, rapid acquisition of test results, accuracy, undemanding to personnel qualifications, relatively small equipment cost, and safety. In the course of the experiment, we obtained a curve of decrease of the free nuclear induction of the H-NMR sample containing a solid and a mobile phase. Graphs of the relative proportion of solid components and liquid phase shows the dependence of the content of cellulose and lignin in the sample and its moisture rate on the percentage of rotten wood.
Keywords: NMR relaxation; cellulose; lignin; rotten wood; pellets